SCRM Analysis of PT. SupermarketBangunan with a Balanced Scorecard Approach - Daniel Hadrian Yohandy; Gilbert Gutabaga Hungilo (Indonesian Journal of Information Systems, 2021)
The use of social media is increasingly varied and full of innovation along with the development of information technology. Initially it was intended as a means of communicating in the digital world and socializing with other people without being limited by distance and time, but now it is starting to have value in the business world. The earliest known and used examples are usage for promotions, advertisements, and info about new services. However, as companies become aware of the value of social relationships with customers, social media is again taking part for companies to maintain relationships with their customers. For business purposes, risk is a problem that must be minimized and even avoided. The application of social media in business is still risky and a standard assessment is needed to assess whether the return value that will be obtained is worth it or not. Therefore, this research uses a case study of a building materials PT in implementing Social Customer Relationship Management in business processes and assesses it using the standards of the Balanced Scorecard.